HUBUNGAN LAMA PEMBERIAN ASI DAN BERAT LAHIR DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIULAK MUKAI KABUPATEN KERINCI TAHUN 2019 - Selfi Angriani; Merita Merita; Aisah Aisah (Universitas Baiturrahim, 2019)
The incidence of stunting in infants is one of the global nutritional problems. The prevalence of stunting in Kerinci Regency on 2017 is 35.0%. The purpose of this study was to determine the relationship between duration of breastfeeding and birth weight with the incidence of stunting in the work area of Community Health Centres of Siulak Mukai in 2019. This study used a cross sectional design that carried out in the work area of Community Health Centres of Siulak Mukai on May, 2019. The population in the study amounted to 311 toddlers. Samples in the study were 74 toddlers with proportional random sampling technique. Data collection was using questionnaire tools and measurement of nutritional status using microtoise. Data was analyzed univariate and bivariate (chi-square test). The results showed that the most had normal nutritional status (Height/Age) (63.5%), duration of breastfeeding ≥2 years (67.6%), and birth weight ≥2500 grams (66.2%). The chi-square analysis showed a significant difference between the duration of breastfeeding and the incidence of stunting (p= 0,000), birth weight with the incidence of stunting (p= 0,000). Therefore, it is expected for mothers of children under five to implement exclusive breastfeeding and continue breastfeeding until the age of 2 years.